When are anti‐fat attitudes understood as prejudice versus truth? An experimental study of social influence effects - G. C. Lee; M. J. Platow; M. Augoustinos; D. Van Rooy; R. Spears; D. Bar‐Tal (Wiley, 2019)
Summary Background/Objectives If people who hold anti‐fat attitudes believe these attitudes to be true, then anti‐prejudice appeals are likely to be unsuccessful, if only because the targets will not see their attitudes as in need of change. The current study examined processes that may lead people to see their anti‐fat attitudes as 'truth' or as 'prejudice'. Subjects/Methods Participants (N = 482) read anti‐fat statements and were then presented with an interpretation of these statements as 'truth' or 'prejudice'. The source of this interpretation was either an (i) in‐group or out‐group member and (ii) expert or non‐expert. Participants' judgements of the statements were expected to vary such that in‐group others and experts would exert more influence than would out‐group others and non‐experts. Results Participants aligned their own interpretations of an anti‐fat statement with those of an expert, but not with those of a non‐expert, F(1,466) = 8.97, p < 0.05, ηp2 = 0.02. The group membership variable had no effect on judgements of 'truth' or 'prejudice' of the anti‐fat statement. Conclusion The expressions that people believe constitute anti‐fat prejudice versus truth about people described as overweight are influenced by exposure to expert opinion (in this case, by medical doctors). Implications for the success of weight‐based anti‐prejudice appeals and for healthcare provision are discussed.